Analisis Penerapan Pengakuan Pendapatan PSAK72 dan Dampak terhadap Pajak Penghasilan Final dan Manajemen Laba pada Perusahaan Kontruksi yang Terdaftar di Bursa Efek Indonesia Tahun 2019. - Adella, Monica; Dewi, Novy Silvia; Ahalik, Ahalik (Journal of Management and Business Review, 2021)
This study aims to determine how the impact of the application of PSAK 72 in construction companies listed in Indonesia Stock Exchange with the assumption that the company did early adoption of PSAK 72 in the 2019 financial statements. PSAK 72 is a standard set by IAI regarding the recognition and measurement of contracts with customers effectively valid on January 1, 2020. The research method used is a qualitative descriptive method by comparing the application of PSAK 34 and PSAK 44 with PSAK 72 in construction companies. Results of this research indicate that the application of PSAK 72 does not have an impact on construction contract but have an impact on real estate contract. Real estate contract must recognition revenue at point in time based on PSAK 72. Real estate contract in PSAK 72 and income tax have difference in revenue recognition and tax imposition. Decreased revenue caused of real estate revenue recognition push management to do earnings management